THE GIVING TOMATO FLOUR (LYCOPERSICON ESCULENTUM) AND TOFU WASTE ON COMMERCIAL FEED TO QUAIL TO EXTERNAL QUALITY OF QUAIL EGG (COTURNIX COTURNIX JAPONICA) LAYER PERIOD - Yusuf, Mochamad; Kardaya, Dede; Sudrajat, Deden (Universitas Djuanda Bogor, 2019)
Tomato (lycopersicon esculentum) is one of Indonesia's local fruits that contain lots of vitamin C and lycopene. Tofu waste is a plant commonly used as an alternative feed to reduce the cost of large feeds. The aims of this research is to find out how far the addition of tomato flour and tofu waste has an influence on the external quality of quail eggs (Coturnix coturnix japanica). The material used in this research was 160 quails, aged 35 weeks with the treatment given : P0 100% control food; P1: 95% control food + 2.5% tomato flour and 2.5% tofu waste; P2: 90% control food + 5% tomato flour and 5% tofu waste; P3: 85% control food + 7.5% tomato flour and 7.5% tofu waste. The design used was Completely Randomized Design (CRD) with 4 treatments and 3 replications with each treatment filled with 13 chickens so that there were 160 quails, then continued with Duncan's multiple range test. Variables observed during the study included egg index, shell thickness and egg weight. The results showed that giving tomato flour and tofu waste to quail feed did not affect the real results on the external quality of quail eggs (egg weight, shell thickness and egg index).Key words : external quality of quail egg, tomato flour, tofu waste